2011
DOI: 10.1093/cercor/bhr292
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Common Neuroanatomical Substrate of Language Deficit between Autism Spectrum Disorder and Specific Language Impairment?

Abstract: Discussion of an overlap between specific language impairment (SLI) and autism spectrum disorder (ASD) is on going. The most intriguing overlap between both phenotypes is the similarity in the observed language deficits described in SLI and a subgroup of ASD with co-occurring linguistic impairment, ASD-LI. Examining whether a similar neuroanatomical substrate underlies this phenotypical linguistic overlap, we studied the white matter microstructural properties of the superior longitudinal fascicle (SLF) of 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
71
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 53 publications
5
71
1
1
Order By: Relevance
“…Age bands were relatively narrow (1–3 years) for studies on children with SD, but wider in studies on children with LD, where three out of four studies reported on groups spanning nine years or greater. Only Verhoeven et al, [20] focused on a narrow age band (all cases were 10 year olds).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Age bands were relatively narrow (1–3 years) for studies on children with SD, but wider in studies on children with LD, where three out of four studies reported on groups spanning nine years or greater. Only Verhoeven et al, [20] focused on a narrow age band (all cases were 10 year olds).…”
Section: Resultsmentioning
confidence: 99%
“…Passive listening to reversed speechNot examinedReduced grey matter:SLI < TD: Medial frontal pole, L + R pSTS ext. to R STG, R medial superior parietal cortex, L occipital pole, R caudate nucleus, R substantia nigra; R pMTGSLI < SIB: L + R par operculum cortex, L occipital poleReduced brain activitySpeech condition:SLI < TD: L IFG (pars orbitalis ); SLI < SIB: L IFG (pars orbitalis); R IFG (pars triangularis); L pSTG;Speech > Reversed Speech:SLI < TD: L pSTG; R putamen; SLI < SIB: L IFG (pars orbitalis)Increased grey matter:SLI > TD: L frontal operculum, R anterior insula, L aIPS;SLI > SIB: L aIPSIncreased brain activityNoneVerhoeven et al, 2012 [20]SLI (mixed receptive-expressive)<3rd centile ≥1 of 3 subtests of Reynell Taaloontwik-kelingsschalen [65], Taaltests voor Kinderen [66], or Schlichting Test voor Taalproductie [67], and PIQ or FS IQ > 80 [68]SLI (n = 13; 10 M)TD (n = 12; 8 M)SLI: 10.1(SD = 0.4)TD for SLI: 10.2(SD = 0.3);DTITractography(SuperiorLongitudinalFasciculus,SLF)In SLI group: WCR subtest and FA both L and R SLF; WCE and left SLFSLI < all TD: Reduced Fractional anisotropy in SLFNo other ROI measuredde Guibert et al, 2011 [27]SLI>1SD below mean for phonology, sentence repetition, and morphosyntactic integration [69, 70], and WISC/WAIS [71, 72] ≥ 70SLI (n = 21, 9 M)TD (n = 18, 9 M)SLI: 11.4 (7–18)TD: 12.7 (8.7–17.7)fMRISilent generation or naming.ROI analysesReduced brain activity:Auditory Response Naming: L pSTG/SMG junctionIncreased brain activityPhonological difference task: R anterior insula ext to IFG opercularis/ triangularis and caudate head.Soriano-Mas et al 2009 [25]DLIRapin [26] classification: Speech programming deficit (n = 5), phonological-syntactic deficit (n = 18), lexical deficit (n = 8), mixed (n = 5)>1SD below mean PPVT [73], TTFC [74], ITPA [75], and WISC-III [76]. IQ > 85.SLI (n = 36; 24 M)TD (n = 36; 24 M)SLI: 10.58(5–17)TD: 10.88 (5–17)VBMOlder SLI : negative correlation btw verbal IQ and GM R perisylvian region, PPVT + GM occipital petaliaNoneIncreased grey matterGlobal volume; R posterior perisylvian, L MOG (occipital petalia)Young SLI > Young TD: L + R entorhinal, L + R temporopolar, L + R caudate nucleus, L + R precentral gyrus, L precuneus, L medial MOGIncreased white matterGlobal volume; Young SLI > Young TD: R medial front cortex, L + R MTGLee et al,2013 [19]Developmental Language Impairment (DLI)>1.5 SD below mean of language composite (word derivations – subtest of TOAL-4, PPVT-4, token test) […”
Section: Resultsmentioning
confidence: 99%
“…Participants were excluded if there was an important medical history or an abnormal neurological examination or if ASD was associated with a genetic syndrome. Participants were recruited from the sample of Verhoeven et al (2012), complemented with additional subjects who fulfilled the same criteria.…”
Section: Participantsmentioning
confidence: 99%
“…Participants were excluded if there was an important medical history or an abnormal neurological examination or if ASD was associated with a genetic syndrome. Participants were recruited from the sample of Verhoeven et al (2012), complemented with additional subjects. As the maximum time delay between current test administration and IQ-testing at the time of study intake was 27 months, and given that IQ scores remain relatively stable at this age (Ramsden et al 2011), no retesting of IQ was performed.…”
Section: Participantsmentioning
confidence: 99%
“…Most participants with ASD (n = 20) had a severe history of early language delay defined by the absence of two-word combinations at the age of three, the presence of language problems during diagnostic assessment and the need for intensive speech therapy during preschool (cf. Verhoeven et al 2012). Three additional participants were added to the ASD sample: they showed poor verbal IQ and a significantly discrepant intelligence profile at the expense of verbal abilities, but early language delay was not formally confirmed for them.…”
Section: Participantsmentioning
confidence: 99%